Molecular determinants of dengue virus type-2 critical for early events in antibody-dependent enhancement of infection - Chotiwan, Nunya, author; Blair, Carol, advisor; Huang, Claire, advisor; Chen, Chaoping, committee member (Colorado State University. Libraries, 2013)
Antibody-dependent enhancement (ADE) of infection might be one of the major factors in the development of more severe forms of dengue disease in patients undergoing a secondary infection of dengue virus (DENV). The ADE is caused by cross-reactivity of subneutralizing or non-neutralizing antibodies (Abs), which form virus-Ab complexes and enhance virus infection by binding to the Fcγ receptors (FCγR) on FcγR-bearing cells. The early events in non-ADE infection have been previously studied, but the virus entry pathway and the DENV molecular determinants involved in ADE are still largely unclear. There are two hypotheses for the early entry pathway of ADE infection: (1) Ab opsonized DENV binds to FcγR and directly enters cells through phagocytic pathway; (2) FcγR plays an auxiliary role in concentrating the opsonized virus to the cell surface, but other cellular receptors are still required for virus entry into the endocytosis pathway. Herein, we investigated contributions of the DENV2 E proteins to ADE infection, as well as the role of FcγRIIA in the enhancement of infection and possible entry route of the Ab-opsonized virion. ADE of wild type (WT) DENV2 infection can be promoted in FcγRIIA-bearing K562 cells by using subneutralizing cross-reactive flaviviral monoclonal antibody (MAb), subcomplex DENV MAb or serotype-specific DENV2 MAb against the E protein, as well as non-neutralizing anti-DENV-prM MAb. The enhancement of infection was analyzed by comparing DENV2 infection under ADE conditions with DENV-Ab complex and non-ADE conditions with DENV alone. Numbers of DENV infected cells were determined by flow cytometry of infected cells stained with labeled MAb 2H2-AlexaFluor-488, while increases in viral output were quantified by qRT-PCR of viral genomes. We investigated multiple DENV mutants generated by reverse genetic technology to identify molecular determinants in the envelope protein (E) of DENV-2 that are critical for DENV attachment and viral-endosomal membrane fusion in both non-ADE and ADE infection of the virus in K562 cells. We determined that binding of virus-Ab complex with FcγRIIA alone is not sufficient for virus entry during ADE infection. Furthermore, the molecular determinants of E protein critical for virus entry and virus-mediated endosomal membrane fusion involved in non-ADE infection were also required for ADE infection. ADE was also tested in FcγRIIA-transfected CV-1 cells (CV-1- FcγRIIA). Surprisingly, no enhancement occurred with any of the tested MAb in this cell type. Numbers of cells expressing FcγRIIA and density of FcγRIIA molecules expressed on CV-1- FcγRIIA cell surface were similar to those of K562 cells. These results supported our findings that FcγRIIA alone was not sufficient to enhance viral infection. The results also suggested that cellular components that are present in K562 cells but absent in CV-1- FcγRIIA cells play a major role in ADE of infection.
Keywords: antibody dependent enhancement; fc gamma receptor; envelope; dengue virus